Exercise Combined with Electrotherapy Enhances Motor Function in an Adolescent with Spinal Muscular Atrophy Type III - Massimiliano Gobbo; Sara Lazzarini; Laura Vacchi; Paolo Gaffurini; Luciano Bissolotti; Alessandro Padovani; Massimiliano Filosto (Case Reports in Neurological Medicine)
Background. Electrotherapy is widely used in physical therapy to increase muscle mass, improve motor function, and assist physical activity in several neurologic conditions. However, concerning Spinal Muscular Atrophy (SMA), limited evidence exists on the role of electrotherapy as an adjunct for improving muscle strength and function. Case Report. An adolescent (13 y.o.) with SMA type III underwent an 18-week strengthening program divided into two stages. During Phase I (weeks: 1-8), a home-based program for quadriceps strengthening through neuromuscular electrical stimulation (NMES) was provided. In Phase II (weeks: 9-18), at-home NMES was combined with functional electrical stimulation (FES) assisting volitional cycling for a broader, systemic conditioning. The treatment improved patient’s structural and functional motor outcomes (quadriceps circumference and strength, Tinetti scale, and Hammersmith scale) as well as independence in stair climbing. Clinical Rehabilitation Impact. The purpose of this report is to raise awareness of the potential role of electrotherapy to help improving motor performance in SMA patients and, secondly, to foster further research aimed at assessing the actual contribution this intervention may have as an add-on therapy to existing care.